The Use of Hamstring Fatigue to Reduce Quadriceps Inhibition After Anterior Cruciate Ligament Reconstruction. Issue 1 (February 2018) - Lowe, Timothy; Dong, Xuanliang Neil
Arthrogenic muscle inhibition, an inability to fully activate the quadriceps muscles, has been persistently observed after anterior cruciate ligament reconstruction (ACLr) surgery. Reductions in quadriceps activation may be partly due to the flexion reflex pathway, hamstrings activation, and reciprocal quadriceps inhibition. Since central fatigue has been shown to modify hamstring excitability and change the hamstring reflex response, hamstring fatigue might alleviate quadriceps muscle inhibition by counteracting the flexion reflex. In this study, nine young adult athletes (age: M = 19.9 years, SD = 1.7) with unilateral ACLr and nine control athletes (age: M = 24.0 years, SD = 2.4) with no previous history of knee injury performed tempo squats to induce fatigue. The ACLr group tended to use hamstrings for more hip flexion and trunk forward flexion than the control group. We assessed each participant's quadriceps inhibition through the central activation ratio (CAR), measured by twitch interpolation, before and after the induced fatigue. A mixed analysis of variance was used to examine the effect of fatigue on the CAR between pre- and post-fatigue and for both ACLr and control groups. The ACLr group showed significantly ( p = .010) greater CAR of the quadriceps post-fatigue ( M = 96.0%, SD = 7.6%) than pre-fatigue ( M = 81.2%, SD = 15.8%), while the control group showed no significant ( p = .969) pre-fatigue ( M = 96.9%, SD = 9.6%) and post-fatigue ( M = 97.0%, SD = 17.1%) differences. Thus, fatigue training may be used as a rehabilitation strategy to restore normal quadriceps function at the knee joint following ACL reconstruction by relaxing the hamstrings and overcoming quadriceps inhibition.